The Influence Of Viral Marketing And Social Media Marketing On Instagram Adds Purchase Decisions - Geofakta Razali; Masfiatun Nikmah; I Nyoman Tri Sutaguna; PA. Andiena Nindya Putri; Muhammad Yusuf (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The purpose of this study is to ascertain how viral marketing and social media advertising impact consumers' purchasing choices on the Instagram Adds platform. The study's sample is made up of Instagram Adds users. The 159 respondents who were sampled were employed in a purposive sampling procedure to get samples. Tests of validity and dependability were run on the research data. The hypothesis test in this study used multiple linear regression tests. According to the conclusions of the first hypothesis test, the test results show that (1) Viral marketing increases purchasing behaviour on the Instagram Adds platform. (2) The results of the testing of the second hypothesis show that social media marketing has an effect on consumers' decisions to make purchases through the Instagram Adds platform.